Histopathological evaluation of duodenal biopsy in the PreventCD project. An observational interobserver agreement study. Issue 3 (26th January 2018) - Villanacci, Vincenzo; Lorenzi, Luisa; Donato, Francesco; Auricchio, Renata; Dziechciarz, Piotr; Gyimesi, Judit; Koletzko, Sibylle; Mišak, Zrinjka; Laguna, Vanesa Morente; Polanco, Isabel; Ramos, David; Shamir, Raanan; et al.
Abstract : Aim of the current study was to evaluate the inter‐observer agreement between pathologists in the diagnosis of celiac disease (CD), in the qualified context of a multicenter study. Biopsies from the "PreventCD" study, a multinational‐ prospective‐ randomized study in children with at least one‐first‐degree relative with CD and positive for HLA‐DQ2/HLA‐DQ8. Ninety‐eight biopsies were evaluated. Considering diagnostic samples with villous atrophy (VA), the agreement was satisfactory (κ = 0.84), but much less when assessing the severity of these lesions. The use of the recently proposed Corazza‐Villanacci classification showed a moderately higher level of agreement (κ = 0.39) than using the Marsh‐Oberhuber system (κ = 0.31). 57.1% of cases were considered correctly oriented. A number of >4 samples per patient was statistically associated to a better agreement; orientation did not impact on κ values. Agreement results in this study appear more satisfactory than in previous papers and this is justified by the involvement of centers with experience in CD diagnosis and by the well‐controlled setting. Despite this, the reproducibility was far from optimal with a poor agreement in grading the severity of VA. Our results stress the need of a minimum of four samples to be assessed by the pathologist.